FATHI YAKAN THE PIONEER OF ISLAMIC ACTIVISM IN LEBANON - Rabil, Robert G. (The levantine review, 2013)
This article explores the ideology of Fathi Yakan, the pioneer of Sunni Islamism in Lebanon and a principal founder of the Islamist party al-‐Jama'a al-‐Islamiya. It also traces the establishment of al_Jama'a as the first organized Islamist party in Lebanon. As Secretary General of al-‐Jama'a, Fathi Yakan blazed the ideological trail for Islamism's participation in Lebanon's political realm. Significantly, Yakan's political activism, in much the same vein as that of Druze "Socialist" Kamal Jumblat, was also more about removing Maronite hegemony over the state.